Combined treatment of ultraviolet‐C and L. plantarum on Salmonella enteritidis and quality control of fresh‐cut apple. Issue 1 (31st May 2017) - Chen, An‐Jun; Luo, Wei; Luo, Yun‐Bo; Zhu, Ben‐Zhong
Abstract: Outbreaks of foodborne illnesses are big problems associated with the consumption of fresh‐cut fruits and vegetables. To enhance the safety of fresh‐cut apples, this study combined ultraviolet (UV) irradiation and lactic acid bacteria (LAB) to eliminate and inhibit the growth of Salmonella enteritidis on fresh‐cut apples. The results showed that the combination treatment of 0.96 kJ/m 2 UV‐C irradiation and subsequently dipping in about 5 log CFU/mL LAB suspension could reduce the population of Salmonella enteritidis by 2.67 ± 0.13 log CFU/g, which was about 2 log more reduction than distilled water treatment (the reduction was 0.36 ± 0.28 log CFU/g). During storage, Salmonella enteritidis remained stable in the combination treatment group while increased up to 5 log CFU/g in the control group. For the quality impact, the combination treatment did not decrease the color, firmness, and flavor of fresh‐cut apples but slightly deteriorated the taste attributes. Practical applications: The markets of fresh‐cut fruits and vegetables have increased rapidly during recent decades. However, the rise of consumption of fresh‐cut fruits and vegetables also increases outbreaks of foodborne illnesses. For the health concerns of chlorine, a commonly used disinfectant, healthier, and efficient methods should to be invented to replace the chlorine treatment. Ultraviolet (UV) light possesses high bactericidal ability and lactic acid bacteria (LAB) can inhibit the growth of other microorganisms during storage. The combination can significantly decrease and inhibit other microorganisms before and during storage. It has a promising prospect to be applied in the fresh‐cut industry.